Malpractice and Medical Liability European State of the Art and Guidelines - Ferrara, Santo Davide.; Boscolo-Berto, Rafael.; Viel, Guido. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Medical responsibility lawsuits have become a fact of life in every physicians medical practice. However, there is evidence that physicians are increasingly practicing defensive medicine, ordering more tests than may be necessary and avoiding patients with complicated conditions. Modern medical practice is increasingly complicated by factors beyond the traditional realm of patient care, including novel technologies, loss of physician autonomy, and economic pressures. A continuing and significant issue affecting physicians and the healthcare system is malpractice. In the latter half of the 20th century, there was a major change in the attitude of the public towards the medical profession. People were made aware of the huge advances in medical technology, because health problems have increasingly tended to attract media interest and wide publicity. Medicine is a victim of its own success in this respect, and people are now led to expect the latest techniques and a perfect outcome on every occasion. This burst of technology and hyper-specialization in many fields of medicine means that each malpractice claim is transformed into a scientific challenge, requiring specific preparation in the analysis and judgment of the clinical case in question. The role of legal medicine has become increasingly specific in this judicial setting, often giving rise to erroneous interpretations and hasty scientific verdicts, but guidelines on the methodology of ascertainments and criteria of evaluation are lacking all over the world. The aim of this book is to clarify the steps required for a sequential, in-depth analysis of events and the consequences of medical actions. This can then be used to verify whether, in the presence of damage, health professionals made errors or failed to observe rules of conduct, and which causal values and links to their possible misconduct are involved.